Peningkatan Daya Tahan dan Daya Tahan Kecepatan melalui Continuous Run dan Interval Training Pada Atlet Remaja Cabang Atletik Jarak Jauh - Mustofa, Latib; Tomoliyus, Tomoliyus; Sukamti, Endang Rini (Jurnal Kepelatihan Olahraga, 2024)
This study aims to determine the level of success in providing continuous running and interval training methods to adolescent athletes in Balikpapan, especially in athletics, as well as to determine the load and portion of training that is appropriate to the athlete's age limit, and find out what the percentage of success is. The training methods that will be used are the continuous running method and interval training methods, including (long slow/recovery, medium, high, interval principles, intensive and extensive). The research method used is quantitative with descriptive statistical techniques. The research population was male youth athletes aged 15 to 16 years in Balikpapan, East Kalimantan. This sample was determined based on purposive sampling. The data collection technique uses test instruments consisting of a 400 m test and a balke test. The technical analysis of research data uses descriptive statistical techniques during 6 months of practice. The author uses a paired sample test with a decision basis if Sig. (2-tailed) 0.05 then there is a significant difference and conversely if Sig, (2-tailed) 0.05 then there is no significance. It is known that the Sig value. (2-tailed) is 0.022 0.05 so the author can conclude that there is a difference between before and after being given speed and endurance training, and can also be seen from the percentage data before treatment of 75% and after treatment of 86%. Conclusion Continuous run and interval training methods are very effective in increasing endurance and are important supports in improving athlete performance.